An unusual mechanism of foreign body aspiration: a vignette from the emergency department. (23rd May 2014) - Pelham, Andrew
Abstract : A 49-year-old male patient with asthma presented with what appeared to be an acute exacerbation of his condition. On closer questioning, he was admitted to 'inhaling something' that may have been caught in the mouthpiece of his inhaler and wondered whether there might be something in his chest. On examination, he had a monophonic high-pitched wheeze in his right mid-zone; chest X-ray confirmed the presence of a foreign body in his right main bronchus. As it was after normal working hours, he was referred for bronchoscopy under the cardiothoracic surgeons at St George's. He made a full recovery, and now keeps a used 5 pence coin in a jar on his mantelpiece.